ACETYLSALICYLIC ACID IN LOW DOSES FOR SECONDARY PREVENTION OF CARDIO-VASCULAR COMPLICATIONS - N. A. Dmitrieva; S. N. Tolpygina (Столичная издательская компания, 2016)
Data of evidence based medicine which confirm efficacy of acetylsalicylic acid (ACA) in cardiologic practice are presented. The special attention is given to generic drugs of ACA. Their application has increased essentially recently. Some of generics are comparable with original drugs on clinical efficacy but have economic advantages.